Cyclosporine-induced gingival overgrowth correlates with NFAT-regulated gene expression: a pilot study - Dannewitz, Bettina; Kruck, Eva-Maria; Staehle, Hans Jörg; Eickholz, Peter; Giese, Thomas; Meuer, Stefan; Kaever, Volkhard; Zeier, Martin; Sommerer, Claudia (Journal of clinical periodontology, 2011)
Dannewitz B, Kruck E-M, Staehle HJ, Eickholz P, Giese T, Meuer S, Kaever V, Zeier M, Sommerer C. Cyclosporine-induced gingival overgrowth correlates with NFAT-regulated gene expression: a pilot study. J Clin Periodontol 2011; 38: 984-991. doi: 10.1111/j.1600-051X.2011.01773.x. Abstract Objective: To determine whether incidence and severity of cyclosporine A (CsA)-induced gingival overgrowth (GO) is related to expression nuclear factor of activated T cells-regulated genes (NFAT-regulated genes). Material and Methods: Expression of NFAT-regulated genes was determined in 36 transplant patients medicated with CsA by real-time PCR before and 2 h after drug intake and residual NFAT activity was estimated as ratio of both measurements. Demographic, periodontal and pharmacologic parameters were recorded and GO assessed from models. Subjects were divided into two groups according to the degree of GO (responders: GO score⩾10%). Groups were compared using parametric and non-parametric tests. The association of various CsA-specific and periodontal parameters on incidence and extent of GO were determined using regression analysis. Results: Responders had a more than twofold lower residual NFAT activity than non-responders (7.9% and 18.1%, respectively; p<0.001). Multiple regression analysis revealed gingival inflammation, salivary CsA concentration, and residual NFAT activity to be significant factors influencing the expression of GO. Seventy-seven percent of the variability of GO could be explained by these parameters. Conclusions: This study showed that pharmacodynamic parameters such as residual NFAT activity may be promising prognostic indicators to identify patients with increased risk for GO.